Pharmacoproteomic characterisation of human colon and rectal cancer. Issue 11 (3rd November 2017) - Frejno, Martin; Zenezini Chiozzi, Riccardo; Wilhelm, Mathias; Koch, Heiner; Zheng, Runsheng; Klaeger, Susan; Ruprecht, Benjamin; Meng, Chen; Kramer, Karl; Jarzab, Anna; Heinzlmeir, Stephanie; Johnstone, Elaine; et al.
Abstract: Most molecular cancer therapies act on protein targets but data on the proteome status of patients and cellular models for proteome‐guided pre‐clinical drug sensitivity studies are only beginning to emerge. Here, we profiled the proteomes of 65 colorectal cancer (CRC) cell lines to a depth of > 10, 000 proteins using mass spectrometry. Integration with proteomes of 90 CRC patients and matched transcriptomics data defined integrated CRC subtypes, highlighting cell lines representative of each tumour subtype. Modelling the responses of 52 CRC cell lines to 577 drugs as a function of proteome profiles enabled predicting drug sensitivity for cell lines and patients. Among many novel associations, MERTK was identified as a predictive marker for resistance towards MEK1/2 inhibitors and immunohistochemistry of 1, 074 CRC tumours confirmed MERTK as a prognostic survival marker. We provide the proteomic and pharmacological data as a resource to the community to, for example, facilitate the design of innovative prospective clinical trials. Synopsis: Deep proteome profiling of colorectal cancer (CRC) cell lines is used to identify cell lines matching to molecular subtypes of CRC patients. The subsequent identification of molecular signatures predicting the response to specific drugs is a useful resource for clinical trial design. The proteomes of 65 CRC cell lines are characterized by quantitative mass spectrometry to a depth of > 10, 000 proteins. A combined analysis of proteomes and transcriptomes of cell lines and patients reveals integrated CRC subtypes. Integration with phenotypic drug sensitivity data predicts subtype‐specific drug response. MERTK protein levels in patients predict response to MEK inhibitors and patient survival. Abstract : Deep proteome profiling of colorectal cancer (CRC) cell lines is used to identify cell lines matching to molecular subtypes of CRC patients. The subsequent identification of molecular signatures predicting the response to specific drugs is a useful resource for clinical trial design.